The relationship between work social support and Work-life balance in hotel industry - Fatahyah, Yahya; Yap, Justina Yen Ying (Institut Penyelidikan Pembangunan Belia Malaysia, 2014)
The purpose of this study is to determine the relationship between work social support and work-life balance in hotel industry. A total number of 87 respondents were selected from a medium-scale hotel located in Kuching, Sarawak. A correlational research design was used in this study with a quantitative method. The result generated by a Pearson Correlation test showed there are positive relationships between all the three independent variables and work-life balance; organizational support (r=+0.44), supervisor support (r=+0.41) and colleagues support (r=+0.45). The significant value (r) concluded the strength of these three relationships is moderate. Based on these findings, several contributions are further discusses. Some recommendations were also suggested for the employer or organization, human resources practitioner and future researcher to encourage work-life balance practice in the workplace.